1998
DOI: 10.1128/iai.66.10.4624-4632.1998
|View full text |Cite
|
Sign up to set email alerts
|

Invasion bySalmonella typhimuriumInduces Increased Expression of the LMP, MECL, and PA28 Proteasome Genes and Changes in the Peptide Repertoire of HLA-B27

Abstract: We have analyzed proteasomal adaptation and associated changes in the B27-bound peptide repertoire in response to cellular invasion withSalmonella. The peptide repertoire of HLA-B27 complexes was analyzed by two different methods: (i) high-pressure liquid chromatography (HPLC) profiles of newly synthesized peptides eluted from B27 following metabolic labeling with arginine and (ii) reactivities with two B27 monoclonal antibodies, Ye-2 and B27.M2, sensitive to peptide-induced conformational changes. LMP, MECL, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 34 publications
1
3
1
Order By: Relevance
“…These results are in contrast with a previous report 15 in which infection of HeLa cells with S. typhimurium increased the reverse transcription‐polymerase chain reaction values of the β 1 i, β 2 i and β 5 i subunits, and the amount of β 1 i protein as detected by Western blot analysis, although in that study the expected changes in the mature proteasomes purified from infected cells were not analysed. These differences might be attributed to the different cell lines used in both studies, and to the different behaviour of the bacteria in both cell types, because S. typhimurium proliferates inside HeLa cells, but not, or very little, inside C1R cells.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These results are in contrast with a previous report 15 in which infection of HeLa cells with S. typhimurium increased the reverse transcription‐polymerase chain reaction values of the β 1 i, β 2 i and β 5 i subunits, and the amount of β 1 i protein as detected by Western blot analysis, although in that study the expected changes in the mature proteasomes purified from infected cells were not analysed. These differences might be attributed to the different cell lines used in both studies, and to the different behaviour of the bacteria in both cell types, because S. typhimurium proliferates inside HeLa cells, but not, or very little, inside C1R cells.…”
Section: Discussioncontrasting
confidence: 99%
“…It has been reported that infection of HeLa cells by S. typhimurium results in an increase of the inducible subunit b 1 i, and concomitant changes in the HLA-B27bound peptide repertoire. 15 Changes in the B27-bound peptide repertoire were also reported in L cells infected with Shigella flexneri. 16 In contrast, in the lymphoid cell line C1R, the HLA-B27-bound peptide repertoires from S. typhimurium-infected and non-infected cells are very similar.…”
Section: Abstract: Antigens; Arthritis; Peptides; Proteasome; Salmonellamentioning
confidence: 88%
See 1 more Smart Citation
“…All of the primer pairs were previously used for the successful detection of each of the genes. 16,17,[30][31][32][33] The sizes of the PCR products were confirmed to be identical to the predicted sizes ( Table 1) by 1.2% agarose gel electrophoresis. The amplification program used was: preheating (95 ° C, 9 min); 35 cycles (95 ° C, 1 min; 55 ° C, 1 min; 72 ° C, 1.5 min); last extension (72 ° C, 10 min).…”
Section: Rna Preparation and Analysis By Rt-pcrsupporting
confidence: 65%
“…The sequences of PCR primers used here are shown in Table 1. All of the primer pairs were previously used for the successful detection of each of the genes 16,17 , 30–33 . The sizes of the PCR products were confirmed to be identical to the predicted sizes (Table 1) by 1.2% agarose gel electrophoresis.…”
Section: Methodsmentioning
confidence: 73%